An analysis of Illocutionary acts in Fantastic Beasts: The Crimes of Grindelwald Movie - Fitriani Fitriani; Masrizal Mahmud; Chairina Nasir (Research in English and Education Journal, 2020)
An illocutionary act is an act that happens when the speaker utters something to the hearer. The purpose of the current research is to find out the types of illocutionary acts dominantly used in the Fantastic Beast:  The Crime of Grindelwald movie spoken by the main character “Newt”. The source of the data was Fantastic Beast: The Crime of Grindelwald movie and the movie script. The research design used in this study was a descriptive qualitative research with documentation analysis as the technique of data collection. In analyzing the data, the researcher used content analysis proposed by Miles Huberman (1994). The research shows that there were 131 illocutionary acts found in the movie. The findings show representative type is the most dominant used by the main character in this movie with 78 data.  The second place is the directive type with 26 data. And then expressive type with 18 data. Commissive type with 8 data and the last type is declarative with only 1 data. Those 131 illocutionary acts are then categorized as types of illocutionary acts proposed by Searle (1969). The results of these Illocutionary acts enhanced the deep meaning in the utterances of the movie mentioned above and made it understandable.